Composite shoe sole with high tensile strength and preparation method thereof
By using the composite structure of ethylene-ethyl acetate, thermoplastic polyurethane, silicane-polysulfonal-polysulfonal ether, and carbon fiber, prepare a composite sole with high resistance, solving the traditional soles of sole materials in resistance. The lack of abrasion resistance realizes the improvement of the lightweight, durability and comfort of the sole.
Patent Information
- Application Number
- CN202411348561.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-28
AI Technical Summary
Traditional casual sole materials have shortcomings in tensile strength, wear resistance and durability, especially in complex and changeable use environments that are prone to cracks, breaks and wear problems.
The composite structure of ethylene-ethylene ethylene parts, thermoplastic polyurethane, silicide-polysulfonate ether modified cluster and carbon fiber and other materials can be prepared by melting mixing, foaming and cooling solidification to prepare high-resistant tensile strength Composite sole.
It significantly improves the resistance and durability of the sole, while maintaining lightweight and good flexibility and comfort, solving the lack of traditional sole materials in terms of resistance and abrasion resistance.
Smart Images

Figure BDA0005061671380000071 
Figure BDA0005061671380000101 
Figure BDA0005061671380000111
Abstract
Description
Technical Field
[0001] The present application relates to the field of casual shoe sole materials, and more specifically, to a composite sole with high tensile strength and a preparation method thereof. Background Art
[0002] As the pace of modern life accelerates, people have higher and higher requirements for comfort and durability in daily wear. Casual shoes are lightweight and comfortable, and have become the first choice for people's daily wear, outdoor activities or travel. In particular, leather casual shoes, because of their stylish and elegant appearance and comfortable wearing experience, can provide a formal, casual and comfortable wearing option even in a more formal business environment.
[0003] Traditional leather casual shoes mostly use single or multi-layer leather, rubber and other materials to make soles, such as EVA (ethylene-vinyl acetate copolymer), which is widely used in the preparation of casual shoe soles. Although these materials can meet the needs of lightness and cost-effectiveness of shoes to a certain extent, they are insufficient in terms of tensile strength, wear resistance and durability. When facing complex and changeable use environments, soles made of a single material are prone to cracks, breaks and wear and tear. Especially for consumers who often participate in outdoor activities or need to stand for a long time, the performance of such soles is often difficult to meet their needs. Therefore, the industry continues to explore the application of composite materials to improve the comprehensive performance of casual shoe soles. Among them, composite soles can give full play to the advantages of each layer of materials through the combination of multiple different materials, so that the tensile strength and wear resistance of the soles can be significantly improved.
[0004] With regard to the above-mentioned related technologies, the inventors found that although the current composite sole technology has made certain progress, there are still some problems to be solved. For example, some manufacturers try to add high-strength fiber materials such as carbon fiber and glass fiber into composite soles. These materials can effectively improve the tensile strength and durability of the soles. However, due to improper material combination or production process defects, the soles are too heavy, and the flexibility and comfort are also affected, which cannot meet consumers' needs for comfort and health. Summary of the invention
[0005] In order to improve the tensile strength and durability of the soles of leather casual shoes while ensuring wearing comfort, the present application provides a composite sole with high tensile strength and a preparation method thereof.
[0006] In a first aspect, the present application provides a composite sole with high tensile strength, which adopts the following technical solution: A composite shoe sole with high tensile strength comprises, by weight, 60-80 parts of ethylene-vinyl acetate copolymer, 20-35 parts of thermoplastic polyurethane, 15-25 parts of siloxane-polysulfide modified copolymer, 0.5-1 parts of foaming agent, 8-14 parts of carbon fiber, 1-2 parts of coupling agent and 1-2 parts of stabilizer.
[0007] By adopting the above-mentioned technical scheme, the composite sole of the present application uses ethylene-vinyl acetate copolymer, thermoplastic polyurethane and siloxane-polysulfide modified copolymer as main raw materials, combined with carbon fiber, to give the sole good tensile strength, durability and wearing comfort. Carbon fiber has the characteristics of low density, which helps to prepare lightweight sole materials and reduce the overall weight of the shoes.
[0008] The siloxane-polysulfide modified copolymer is an interpenetrating polymer network structure formed by the mutual penetration and entanglement of siloxane prepolymer and polysulfide prepolymer. This interpenetrating network structure makes the two polymer networks tightly combined at the microscopic level. As the raw material of the sole material, it can effectively disperse the stress generated by the sole when it is subjected to external force, prevent the sole from cracking, breaking and other phenomena caused by local stress concentration, and enhance the tensile strength of the sole.
[0009] The good weather resistance and lubricity of siloxane combined with the excellent strength and chemical corrosion resistance of polysulfide can effectively reduce the material wear and fatigue caused by the use of the sole in friction and various complex environments, effectively extending the service life of the sole.
[0010] In addition, the good lubricity of the modified copolymer of the interpolymerized network structure of siloxane and polysulfide enables it to well infiltrate the carbon fiber, fully penetrate into the pores and surface of the carbon fiber, and form a tight bonding layer between the carbon fiber and other sole materials. The polymers of siloxane and polysulfide have good flexibility, which can improve the adverse effects of rigid fillers on the flexibility of the sole, and can give the sole good elasticity and cushioning properties while improving the tensile strength of the sole, ensuring flexibility and comfort of wearing.
[0011] Optionally, the raw materials of the siloxane-polysulfide modified copolymer include, by weight, 15-25 parts of methyltrimethoxysilane, 3-7 parts of 2-mercaptoethanol, 10-15 parts of 1,2-ethanedithiol, 1-2 parts of a crosslinking agent, 0.1-0.3 parts of an organic tin catalyst, 0.1-0.3 parts of dibenzoyl peroxide, and 0.5-1 parts of azobisisobutyronitrile.
[0012] By adopting the above technical scheme, methyltrimethoxysilane is used as the raw material of siloxane, 2-mercaptoethanol and 1,2-ethanedithiol are used as the raw materials of polysulfide, and siloxane and polysulfide form a close interface bonding during the interpenetration process, forming an interpenetrating network structure with good flexibility, which is beneficial to the uniform distribution and transmission of stress and improves the mechanical properties of the overall material.
[0013] Optionally, the preparation method of the siloxane-polysulfide modified copolymer comprises the following steps: Mixing methyltrioxysilane and an organic tin catalyst, mixing with ethanol at a solid-liquid ratio of 1:(2-5), adjusting the pH to 3-4, and performing hydrolysis and condensation reaction at 70-80° C. for 6-8 hours to obtain a siloxane prepolymer; Mix 2-mercaptoethanol, 1,2-ethanedithiol and dibenzoyl peroxide in a mass ratio of 1:(2-3) with ethanol, and perform free radical polymerization at 120-140° C. for 6-8 hours to obtain a polysulfide prepolymer; The siloxane prepolymer and the polysulfide prepolymer are mixed uniformly in a mass ratio of , azobisisobutyronitrile and a crosslinking agent are added, the pH is adjusted to 3-4, heated and stirred at 80-100° C. in an inert gas atmosphere, and reacted for 18-20 hours to obtain a siloxane-polysulfide interpenetrating polymer network stock solution; The siloxane-polysulfide interpenetrating polymer network stock solution is vacuum dried at 60-70° C. for 24-30 hours to obtain the product.
[0014] By adopting the above technical solution and accurately designing the process parameters, the formation of the siloxane-polysulfide interpenetrating network structure is effectively promoted through processes such as hydrolysis condensation, free radical polymerization, catalysis and drying. The preparation process is simple and can be promoted on a large scale.
[0015] Optionally, the crosslinking agent is any one of 3-(methacryloyloxy)propyltrimethoxysilane and γ-glycidyloxypropyltrimethoxysilane.
[0016] By adopting the above technical scheme, the molecular structure of 3-(methacryloyloxy)propyltrimethoxysilane and γ-glycidyloxypropyltrimethoxysilane contains epoxy and methoxysilane, which can react with hydroxyl, carboxyl, silanol and other groups in siloxane and polysulfide to form more stable chemical bonds, effectively promote the cross-linking of siloxane and polysulfide chain segments, and enhance the overall strength and stability of the material.
[0017] Optionally, the organic tin catalyst is any one of dibutyltin dilaurate, dibutyltin dilaurate, and stannous octoate.
[0018] By adopting the above technical scheme, dibutyltin dilaurate, tetraalkyltin compounds, dibutyltin dilaurate, and stannous octoate are all organic tin catalysts, which can efficiently catalyze the hydrolysis and condensation of methyltrimethoxysilane to form siloxane segments under acidic conditions.
[0019] Optionally, the stabilizer includes an antioxidant and a light stabilizer in a mass ratio of (1-3):1.
[0020] By adopting the above technical solution, the combined use of antioxidants and light stabilizers can effectively prevent the material from aging due to oxidation and light during use, thereby extending the service life of the product.
[0021] Optionally, the antioxidant is selected from any one of antioxidant 1010, antioxidant 1076, and antioxidant 168; the light stabilizer is selected from any one of light stabilizer UV-326, light stabilizer UV-531, light stabilizer UV-770, and light stabilizer UV-971.
[0022] Optionally, the foaming agent is selected from any one or more combinations of azodicarbonamide, 4,4-oxobisbenzenesulfonylhydrazide, N,N-dinitrosopentamethylenetetramine and sodium bicarbonate.
[0023] In a second aspect, the present application provides a method for preparing a composite sole with high tensile strength, using the following technical solution: A method for preparing a composite sole with high tensile strength comprises the following steps: Ethylene-vinyl acetate copolymer, thermoplastic polyurethane, siloxane-polysulfide modified copolymer, foaming agent, carbon fiber and stabilizer are uniformly mixed according to a proportion, and melt-mixed at 130-150° C. for 30-50 minutes to form a melt; The melt is injected into a pre-designed sole mold and foamed at 120-160°C and 8-10MPa to form the initial shape of the sole; The foamed sole is cooled and solidified, and then polished and repaired.
[0024] By adopting the above technical scheme, through the steps of melt mixing, foaming molding, cooling and solidification, a sole with a uniform structure and a predetermined shape can be obtained, thereby achieving efficient production of composite soles and ensuring product consistency and high quality.
[0025] Optionally, the carbon fibers are pre-treated as follows before mixing: The carbon fiber and the silane coupling agent are mixed in a mass ratio of 1:(0.1-0.3), added into an ethanol solution in a material-liquid ratio of 1:(5-7), stirred at 70-80°C for 1-2h, and then dried to obtain modified carbon fiber.
[0026] By adopting the above technical solution, the carbon fiber is surface treated and modified by a silane coupling agent. The silanol of the coupling agent can react with the hydroxyl group on the surface of the carbon fiber to form a stable Si-OC bond. At the same time, the organic part of the coupling agent is compatible with other polymer matrices, thereby improving the bonding force between the raw materials.
[0027] In summary, this application has the following beneficial effects: 1. Since the raw materials of the present application contain siloxane-polysulfide modified copolymers, which have good flexibility and lubricity, the carbon fibers can be fully impregnated with the surface and pores, making the carbon fibers more stably and evenly dispersed, and forming a closer bond with the raw materials, thus significantly improving the adverse effects of rigid fillers on the flexibility of the sole, improving the elasticity and cushioning properties of the sole, and ensuring the flexibility and comfort of wearing.
[0028] 2. In the present application, the siloxane and polysulfide chain segments penetrate and entangle with each other to form a siloxane-polysulfide interpenetrating polymer network structure. This network structure enhances the compatibility between the composite sole raw materials, making the overall structure more compact and stable. It can effectively disperse and transfer stress when subjected to external force, reduce defects in the composite sole system at the microscopic level, and significantly improve the tensile strength and durability of the sole.
[0029] 3. The method of the present application is simple and feasible, easy to operate and control, can be carried out on a large scale, and realizes the efficient production of composite soles. DETAILED DESCRIPTION
[0030] The following examples further illustrate the present application in detail.
[0031] raw material Unless otherwise specified, the raw materials used in the preparation examples, embodiments and comparative examples in this application are all commercially available products, specifically: Methyltrimethoxysilane, selected from Rishengchang New Materials, 1185-55-3; 2-Mercaptoethanol, selected from Jizhi Chemical, TCL-M0058; 1,2-ethanedithiol, selected from Xinxin Jiali Biotechnology, E44105; Dibenzoyl peroxide, selected from Jizhi Chemical, B83771; Azobisisobutyronitrile, selected from Jizhi Chemical, A21900; 3-(Methacryloyloxy)propyltrimethoxysilane, selected from Alpha, A530850; γ-Glycidyloxypropyltrimethoxysilane, selected from Dulai Biotechnology, SAA0031-1; Dibutyltin dilaurate, selected from Tosoh Chemical, CAS: 77-58-7; Dibutyltin dilaurate, selected from Tesco Chemicals, 2022062710; Stannous octoate, selected from Merck, S3252; Ethylene-vinyl acetate copolymer, selected from Dow EVA360; Thermoplastic polyurethane, selected from BASF M353; Azodicarbonamide, selected from Runfeng, 123-77-3.
[0032] Preparation Example of Siloxane-Polysulfide Modified Copolymer Preparation Example 1 Siloxane-polysulfide modified copolymer, the raw materials and amounts are shown in Table 1, wherein the crosslinking agent is γ-glycidyloxypropyltrimethoxysilane, and the organic tin catalyst is dibutyltin dilaurate.
[0033] Table 1 Components Preparation Example 1 Preparation Example 2 Preparation Example 3 Preparation Example 4 Methyltrimethoxysilane / g 17 15 22 25 2-Mercaptoethanol / g 3 7 5 6 1,2-Ethanedithiol / g 15 10 12 13 Crosslinking agent / g 1.2 1 1.7 2 Organotin catalyst / g 0.1 0.2 0.25 0.3 Dibenzoyl peroxide / g 0.1 0.1 0.3 0.2 Azobisisobutyronitrile / g 0.5 0.6 0.8 1 The preparation method of the above-mentioned siloxane-polysulfide modified copolymer comprises the following steps: S1: Methyltrioxysilane and an organic tin catalyst are mixed, and then mixed with ethanol at a solid-liquid ratio of 1:3, and the pH is adjusted to 4, and a hydrolysis and condensation reaction is carried out at 70° C. for 6 hours to obtain a siloxane prepolymer; S2: 2-mercaptoethanol, 1,2-ethanedithiol and dibenzoyl peroxide in a mass ratio of 1:3 are mixed with ethanol, and a free radical polymerization reaction is carried out at 140° C. for 6 hours to obtain a polysulfide prepolymer; S3: uniformly mixing a siloxane prepolymer and a polysulfide prepolymer in a mass ratio of , adding azobisisobutyronitrile and a crosslinking agent, adjusting the pH to 3, heating and stirring at 90° C. in an inert gas atmosphere, and reacting for 20 hours to obtain a siloxane-polysulfide interpenetrating polymer network stock solution; S4: The siloxane-polysulfide interpenetrating polymer network stock solution is dried under vacuum at 70° C. for 24 h to obtain.
[0034] Preparation Example 2 The difference between the siloxane-polysulfide modified copolymer and the preparation example 1 is that the raw materials and the amounts used are shown in Table 1; The preparation method of the above-mentioned siloxane-polysulfide modified copolymer comprises the following steps: S1: Methyltrioxysilane and an organic tin catalyst are mixed, mixed with ethanol at a solid-liquid ratio of 1:2, the pH is adjusted to 4, and hydrolysis and condensation reaction is carried out at 70° C. for 7 hours to obtain a siloxane prepolymer; S2: 2-mercaptoethanol, 1,2-ethanedithiol and dibenzoyl peroxide in a mass ratio of 1:3 are mixed with ethanol, and a free radical polymerization reaction is carried out at 120° C. for 8 hours to obtain a polysulfide prepolymer; S3: uniformly mixing a siloxane prepolymer and a polysulfide prepolymer in a mass ratio of , adding azobisisobutyronitrile and a crosslinking agent, adjusting the pH to 3, heating and stirring at 100° C. in an inert gas atmosphere, and reacting for 18 h to obtain a siloxane-polysulfide interpenetrating polymer network stock solution; S4: The siloxane-polysulfide interpenetrating polymer network stock solution is dried under vacuum at 70° C. for 28 h to obtain.
[0035] Preparation Example 3 The siloxane-polysulfide modified copolymer is different from that of Preparation Example 1 in that the raw materials and amounts are as shown in Table 1, wherein the crosslinking agent is 3-(methacryloyloxy)propyltrimethoxysilane, and the organic catalyst is dibutyltin dilaurate; The preparation method of the above-mentioned siloxane-polysulfide modified copolymer comprises the following steps: S1: Methyltrioxysilane and an organic tin catalyst are mixed, mixed with ethanol at a solid-liquid ratio of 1:5, the pH is adjusted to 3, and hydrolysis and condensation reaction is carried out at 80° C. for 8 h to obtain a siloxane prepolymer; S2: 2-mercaptoethanol, 1,2-ethanedithiol and dibenzoyl peroxide in a mass ratio of 1:2 are mixed with ethanol, and a free radical polymerization reaction is carried out at 130° C. for 8 hours to obtain a polysulfide prepolymer; S3: uniformly mixing a siloxane prepolymer and a polysulfide prepolymer in a mass ratio of , adding azobisisobutyronitrile and a crosslinking agent, adjusting the pH to 4, heating and stirring at 80° C. in an inert gas atmosphere, and reacting for 18 h to obtain a siloxane-polysulfide interpenetrating polymer network stock solution; S4: The siloxane-polysulfide interpenetrating polymer network stock solution is dried under vacuum at 60° C. for 30 h to obtain.
[0036] Preparation Example 4 The difference between the siloxane-polysulfide modified copolymer and the preparation example 1 is that the raw materials and the amounts used are as shown in Table 1, wherein the organic tin catalyst is stannous octoate; The preparation method of the above-mentioned siloxane-polysulfide modified copolymer comprises the following steps: S1: Methyltrioxysilane and an organic tin catalyst are mixed, mixed with ethanol at a solid-liquid ratio of 1:4, the pH is adjusted to 3, and hydrolysis and condensation reaction is carried out at 75° C. for 8 hours to obtain a siloxane prepolymer; S2: 2-mercaptoethanol, 1,2-ethanedithiol and dibenzoyl peroxide in a mass ratio of 1:2 are mixed with ethanol, and a free radical polymerization reaction is carried out at 130° C. for 7 hours to obtain a polysulfide prepolymer; S3: uniformly mixing a siloxane prepolymer and a polysulfide prepolymer in a mass ratio of , adding azobisisobutyronitrile and a crosslinking agent, adjusting the pH to 3, heating and stirring at 100° C. in an inert gas atmosphere, and reacting for 20 hours to obtain a siloxane-polysulfide interpenetrating polymer network stock solution; S4: The siloxane-polysulfide interpenetrating polymer network stock solution is dried under vacuum at 60° C. for 26 h to obtain. Example
[0037] Example 1 A composite sole with high tensile strength, the raw materials and amounts are shown in Table 2, wherein the siloxane-polysulfide modified copolymer is obtained from Preparation Example 1; carbon fiber, density 1.75 g / cm 3 , an average diameter of 7 μm, and an aspect ratio of (2-8):1; the silane coupling agent is γ-glycidyloxypropyltrimethoxysilane; the stabilizer includes antioxidant 1010 and light stabilizer UV-326 in a mass ratio of 1:1; and the foaming agent is azodicarbonamide.
[0038] Table 2 The method for preparing the composite sole with high tensile strength comprises the following steps: S1: mixing carbon fiber and silane coupling agent in a mass ratio of 1:0.2, adding them to an ethanol solution in a material-liquid ratio of 1:6, stirring at 80° C. for 1 h, and then drying to obtain modified carbon fiber; S2: adding ethylene-vinyl acetate copolymer, thermoplastic polyurethane, siloxane-polysulfide modified copolymer, foaming agent, modified carbon fiber and stabilizer into a high-speed mixer according to a proportion and mixing them evenly, and then placing them in a melter, setting the melter temperature to 140° C. and heating and melting for 30 minutes until they are in a molten state to form a melt; S3: injecting the melt into a pre-designed sole mold, and performing foaming molding at 150° C. and 10 MPa to form a preliminary shape of the sole; S4: placing the foamed sole in a cooling system for cooling and solidification, and then grinding and repairing it.
[0039] Example 2 A composite shoe sole with high tensile strength, which is different from Example 1 in that the raw materials and the amounts thereof are as shown in Table 2, wherein the stabilizer comprises an antioxidant 1076 and a light stabilizer UV-531 in a mass ratio of 2:1; and the foaming agent is 4,4-oxybisbenzenesulfonyl hydrazide; and the preparation method of the composite shoe sole with high tensile strength comprises the following steps: S1: mixing carbon fiber and silane coupling agent in a mass ratio of 1:0.1, adding them to an ethanol solution in a material-liquid ratio of 1:7, stirring at 70° C. for 2 h, and then drying to obtain modified carbon fiber; S2: adding ethylene-vinyl acetate copolymer, thermoplastic polyurethane, siloxane-polysulfide modified copolymer, foaming agent, modified carbon fiber and stabilizer into a high-speed mixer according to a proportion and mixing them evenly, and then placing them in a melter, setting the melter temperature to 150° C. and heating and melting for 30 minutes until they are in a molten state to form a melt; S3: injecting the melt into a pre-designed sole mold, and performing foaming molding at 140° C. and 10 MPa to form a preliminary shape of the sole; S4: placing the foamed sole in a cooling system for cooling and solidification, and then grinding and repairing it.
[0040] Example 3 A composite shoe sole with high tensile strength, which is different from Example 1 in that the raw materials and their amounts are as shown in Table 2, wherein the stabilizer comprises antioxidant 168 and light stabilizer UV-770 in a mass ratio of 3:1; the foaming agent is N,N-dinitrosopentamethylenetetramine; The method for preparing the composite sole with high tensile strength comprises the following steps: S1: mixing carbon fiber and silane coupling agent in a mass ratio of 1:0.3, adding them to an ethanol solution in a material-liquid ratio of 1:5, stirring at 80° C. for 2 h, and then drying to obtain modified carbon fiber; S2: adding ethylene-vinyl acetate copolymer, thermoplastic polyurethane, siloxane-polysulfide modified copolymer, foaming agent, modified carbon fiber and stabilizer into a high-speed mixer according to a proportion and mixing them evenly, and then placing them in a melter, setting the melter temperature to 130° C. and heating and melting for 50 minutes until they are in a molten state to form a melt; S3: injecting the melt into a pre-designed sole mold, and performing foaming molding at 120° C. and 10 MPa to form a preliminary shape of the sole; S4: placing the foamed sole in a cooling system for cooling and solidification, and then grinding and repairing it.
[0041] Example 4 A composite shoe sole with high tensile strength, which is different from Example 1 in that the raw materials and their amounts are as shown in Table 2, wherein the stabilizer comprises antioxidant 168 and light stabilizer UV-971 in a mass ratio of 3:1; the foaming agent comprises azodicarbonamide and sodium bicarbonate in a mass ratio of 1:1; The method for preparing the composite sole with high tensile strength comprises the following steps: S1: mixing carbon fiber and silane coupling agent in a mass ratio of 1:0.3, adding them to an ethanol solution in a material-liquid ratio of 1:6, stirring at 70° C. for 1.5 h, and then drying to obtain modified carbon fiber; S2: adding ethylene-vinyl acetate copolymer, thermoplastic polyurethane, siloxane-polysulfide modified copolymer, foaming agent, modified carbon fiber and stabilizer into a high-speed mixer according to a proportion and mixing them evenly, and then placing them in a melter, setting the melter temperature to 150° C. and heating and melting for 40 minutes until they are in a molten state to form a melt; S3: injecting the melt into a pre-designed sole mold, and performing foaming molding at 160° C. and 8 MPa to form a preliminary shape of the sole; S4: placing the foamed sole in a cooling system for cooling and solidification, and then grinding and repairing it.
[0042] Example 5 A composite sole with high tensile strength, which is different from Example 1 in that the raw materials and amounts are as shown in Table 2, and the other steps are the same as those in Example 1.
[0043] Example 6 A composite shoe sole with high tensile strength, which is different from Example 1 in that the siloxane-polysulfide modified copolymer in the raw material is obtained from Preparation Example 2, and the other steps are the same as Example 1.
[0044] Example 7 A composite shoe sole with high tensile strength, which is different from Example 1 in that the siloxane-polysulfide modified copolymer in the raw material is obtained from Preparation Example 3, and the other steps are the same as Example 1.
[0045] Example 8 A composite shoe sole with high tensile strength, which is different from Example 1 in that the siloxane-polysulfide modified copolymer in the raw material is obtained from Preparation Example 4, and the other steps are the same as Example 1.
[0046] Example 9 A composite shoe sole with high tensile strength, which differs from Example 1 in that the carbon fiber is not subjected to the pretreatment modification of step S1, and the other steps are the same as those of Example 1.
[0047] Comparative Example Comparative Example 1 A composite sole with high tensile strength, which differs from Example 1 in that no carbon fiber is added, the carbon fiber in the raw material is replaced by ethylene-vinyl acetate copolymer of equal mass, and the other steps are the same as Example 1.
[0048] Comparative Example 2 A composite shoe sole with high tensile strength, which differs from Example 1 in that no siloxane-polysulfide modified copolymer is added, the siloxane-polysulfide modified copolymer in the raw material is replaced by an ethylene-vinyl acetate copolymer of equal mass, and the other steps are the same as Example 1.
[0049] Performance testing The high tensile strength composite soles obtained in Examples 1-9 and Comparative Examples 1-2 were subjected to durability test. Each test was performed 3 times, and the average value of the 3 tests was taken as the final result. The final test results are recorded in Table 3. The relevant test methods are as follows: 1. Density: Density test is carried out according to GB / T 533 standard; 2. Tensile strength: Refer to the method standard of GB / T 6344-2008 and conduct a mild tensile test on the composite sole; 3. Folding resistance: Cut an opening with a length of 4 mm and a depth of 1 mm on the surface of the composite sole, bend the composite sole along the direction of the cut, and complete one bend when the two ends of the composite sole touch each other. After bending 300,000 times, measure the length of the opening again; 4. Resilience: Refer to the method standard of GB / T 1681-2009 to test the elasticity of the composite sole; 5. Wear resistance: The test was carried out using a DIN abrasion testing machine. The prepared rubber sole material was made into a cylindrical sample with a diameter of 16 mm and a thickness of 8 mm. Under the test conditions of a friction distance of 40 m and a load of 10 N, the transversely moving sample was rubbed against the gauze on the drum, and the wear resistance of the sample was represented by the wear volume of the outsole.
[0050] Table 3 According to the performance test results in Table 3, it can be seen that the composite sole prepared by the preparation method of the present application has high tensile strength, good folding resistance and wear resistance, which shows that the composite sole of the present application has good tensile strength and durability, and when used to prepare leather casual shoes, it overcomes the deficiencies of traditional composite soles in tensile strength, wear resistance and durability. At the same time, the composite sole of the present application has the characteristics of light weight and good resilience, which shows that the high tensile strength composite sole of the present application ensures light weight, good flexibility and comfort while ensuring excellent mechanical properties.
[0051] It can be seen from the performance test results of Examples 1-8 and Example 9 that by surface modification of the carbon fiber with a silane coupling agent, a stable Si-OC bond is formed on the surface of the carbon fiber, which significantly improves the compatibility between the carbon fiber and the polymer matrix, and further improves the mechanical properties of the composite sole, such as tensile strength and wear resistance.
[0052] According to the performance test results of Examples 1-8 and Comparative Examples 1-2, it can be seen that the addition of the siloxane-polysulfide modified copolymer further improves the tensile strength and durability of the composite sole, while ensuring the flexibility and comfort of the composite sole, significantly improving the adverse effects of carbon fiber on the flexibility of the sole, improving the elastic cushioning performance of the sole, and ensuring flexibility and comfort of wearing.
[0053] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A composite sole with high tensile strength, characterized in that: In parts by weight, the raw materials include 60-80 parts of ethylene-vinyl acetate copolymer, 20-35 parts of thermoplastic polyurethane, 15-25 parts of siloxane-polysulfide modified copolymer, 0.5-1 part of foaming agent, 8-14 parts of carbon fiber and 1-2 parts of stabilizer.
2. The high tensile strength composite sole according to claim 1, characterized in that: The raw materials of the siloxane-polysulfide modified copolymer include, by weight, 15-25 parts of methyltrimethoxysilane, 3-7 parts of 2-mercaptoethanol, 10-15 parts of 1,2-ethanedithiol, 1-2 parts of a crosslinking agent, 0.1-0.3 parts of an organic tin catalyst, 0.1-0.3 parts of dibenzoyl peroxide and 0.5-1 parts of azobisisobutyronitrile.
3. The high tensile strength composite sole according to claim 2, characterized in that: The preparation method of the siloxane-polysulfide modified copolymer comprises the following steps: Mixing methyltrioxysilane and an organic tin catalyst, mixing with ethanol at a solid-liquid ratio of 1:(2-5), adjusting the pH to 3-4, and performing hydrolysis and condensation reaction at 70-80° C. for 6-8 hours to obtain a siloxane prepolymer; Mix 2-mercaptoethanol, 1,2-ethanedithiol and dibenzoyl peroxide in a mass ratio of 1:(2-3) with ethanol, and perform free radical polymerization at 120-140° C. for 6-8 hours to obtain a polysulfide prepolymer; The siloxane prepolymer and the polysulfide prepolymer are mixed uniformly in a mass ratio of , azobisisobutyronitrile and a crosslinking agent are added, the pH is adjusted to 3-4, heated and stirred at 80-100° C. in an inert gas atmosphere, and reacted for 18-20 hours to obtain a siloxane-polysulfide interpenetrating polymer network stock solution; The siloxane-polysulfide interpenetrating polymer network stock solution is vacuum dried at 60-70° C. for 24-30 hours to obtain the product.
4. The high tensile strength composite sole according to claim 2, characterized in that: The crosslinking agent is any one of 3-(methacryloyloxy)propyltrimethoxysilane and γ-glycidyloxypropyltrimethoxysilane.
5. The high tensile strength composite sole according to claim 2, characterized in that: The organic tin catalyst is any one of dibutyltin dilaurate, dibutyltin dilaurate, and stannous octoate.
6. The high tensile strength composite sole according to claim 1, characterized in that: The stabilizer includes an antioxidant and a light stabilizer in a mass ratio of (1-3):
1.
7. The high tensile strength composite sole according to claim 6, characterized in that: The antioxidant is selected from any one of antioxidant 1010, antioxidant 1076, and antioxidant 168; the light stabilizer is selected from any one of light stabilizer UV-326, light stabilizer UV-531, light stabilizer UV-770, and light stabilizer UV-971.
8. The high tensile strength composite sole according to claim 1, characterized in that: The foaming agent is selected from any one or more combinations of azodicarbonamide, 4,4-oxobisbenzenesulfonylhydrazide, N,N-dinitrosopentamethylenetetramine and sodium bicarbonate.
9. The method for preparing a composite sole with high tensile strength according to any one of claims 1 to 8, characterized in that: The following steps are involved: Ethylene-vinyl acetate copolymer, thermoplastic polyurethane, siloxane-polysulfide modified copolymer, foaming agent, carbon fiber and stabilizer are uniformly mixed according to a proportion, and melt-mixed at 130-150° C. for 30-50 minutes to form a melt; The melt is injected into a pre-designed sole mold and foamed at 120-160°C and 8-10MPa to form the initial shape of the sole; The foamed sole is cooled and solidified, and then polished and repaired.
10. The method for preparing a composite sole with high tensile strength according to claim 9, characterized in that: The carbon fibers are pre-treated as follows before mixing: The carbon fiber and the silane coupling agent are mixed in a mass ratio of 1:(0.1-0.3), added into an ethanol solution in a material-liquid ratio of 1:(5-7), stirred at 70-80°C for 1-2h, and then dried to obtain modified carbon fiber.